Image‐based modeling and scoring of Howell–Jolly Bodies in human erythrocytes. Issue 3 (24th May 2017) - Angay, Oguzhan; Friedrich, Mike; Pinnecker, Jürgen; Hintzsche, Henning; Stopper, Helga; Hempel, Klaus; Heinze, Katrin G.
Abstract: The spleen selectively removes cells with intracellular inclusions, for example, detached nuclear fragments in circulating erythrocytes, called Howell–Jolly Bodies (HJBs). With absent or deficient splenic function HJBs appear in the peripheral blood and can be used as a simple and non‐invasive risk‐indicator for fulminant potentially life‐threatening infection after spleenectomy. However, it is still under debate whether counting of the rare HJBs is a reliable measure of splenic function. Investigating HJBs in premature erythrocytes from patients during radioiodine therapy gives about 10 thousand times higher HJB counts than in blood smears. However, we show that there is still the risk of false‐positive results by unspecific nuclear remnants in the prepared samples that do not originate from HJBs, but from cell debris residing above or below the cell. Therefore, we present a method to improve accuracy of image‐based tests that can be performed even in non‐specialized medical institutions. We show how to selectively label HJB‐like clusters in human blood samples and how to only count those that are undoubtedly inside the cell. We found a "critical distance" d crit referring to a relative HJB‐Cell distance that true HJBs do not exceed. To rule out false‐positive counts we present a simple inside‐outside‐rule based on d crit —a robust threshold that can be easily assessed by combining conventional 2D imaging and straight‐forward image analysis. Besides data based on fluorescence imaging, simulations of randomly distributed HJB‐like objects on realistically modelled cell objects demonstrate the risk and impact of biased counting in conventional analysis. © 2017 The Authors. Cytometry Part A published by Wiley Periodicals, Inc. on behalf of ISAC.